DEVELOPING ICT-BASED MEDIA FOR TEACHING STRUCTURE ON STUDENTS AT ENGLISH EDUCATION STUDY PROGRAM UNIVERSITY OF PALANGKA RAYA - Usop, Dwima Putra; Luardini, Maria; Asi, Natalina (Journal Compound: Improving the Quality of English Education, 2020)
This research was aimed to develop the ICT-based media for teaching English structure on the students at English education Study Program University of Palangka Raya. This research used Research and Development (R and D). The subject of this research was the students from Basic English Grammar class at English education Study Program University of Palangka Raya. The collected data were analyzed and described qualitatively and quantitatively. The result of data analysis showed that students and the lecturer required relevant media to support the teaching learning activity in COVID-19 pandemic. Considering to those result, the product of this research was the E-learning website named swimsenglishedu.com. The result of expert validation showed that the swimsenglishedu.com were valid. The data obtained from observation showed that the swimsenglishedu.com were helpful for the lecturer to teach English structure. The students were helpful and excited to learn English structure using it. The hypothesis testing that conducted to measure the effectiveness of the developed media also showed that there was a significance effect of swimsenglishedu.com at Basic English Grammar Class of English Education Study Program University of Palangka Raya. The lecturer also could make the swimsenglishedu.com as one of the references media in teaching English structure.